Poverty alleviation: the Indian experience (6th plan 1980-85) - Lal, G. Morley Mohan (Bombay, 1988)
The present analysis is a systematic examination of these questions and of how far anti-poverty programmes have fared during the 6th Plan period. It is natural for a programme of this magnitude to have some ups and downs in the planning, administration and implementing process. But should this provide shelter or excuse always as is the common view that after all IRDP is still only an experiment-a costly experiment indeed in terms of men and money expended? What doubt is there that accountability, competence, higher productivity and managerial abilities will have to be built in the programme personnel and strict vigil and controls wherever necessary will have to be exercised at the appropriate time.
Keywords: Poverty